Does geographic spending variation exacerbate healthcare benefit inequality? A benefit incidence analysis for Indonesia. Issue 7 (2nd June 2021) - Sambodo, Novat Pugo; Van Doorslaer, Eddy; Pradhan, Menno; Sparrow, Robert
Abstract: The Indonesian government has made some ambitious steps to achieve Universal Health Coverage through the newly formed National Health Insurance [ Jaminan Kesehatan Nasional (JKN)], establishing a single-payer insurance agency and prospective provider payment mechanism. This study aims to assess the benefit incidence of healthcare funding in the JKN era, and its distribution by socio-economic status considering regional variation in unit costs. We evaluate whether the benefit incidence of funding is skewed towards urban and wealthier households. We also investigate whether standard benefit incidence analysis using national unit costs underestimates regional disparities in healthcare funding. Lastly, we examine whether the design of the JKN provider payment system exacerbates regional inequalities in healthcare funding and treatment intensity. The analysis relies on Indonesia's annual National Socio-economic Survey (Susenas) and administrative data on JKN provider payments from 2015 to 2017, combined at district level for 466 districts. We find that the benefit incidence of healthcare expenditure favours the wealthier groups. We also observe substantial variation in hospital unit costs across regions in Indonesia. As a result, standard benefit incidence analysis (using national average unit transfers) underestimates the inequality due to regional disparities in healthcare supply and intensity of treatment. The JKN provider payment seems to favour relatively wealthier regions that harbour more advanced healthcare services. Urban dwellers and people living in Java and Bali also enjoy greater healthcare benefit incidence compared to rural areas and the other islands.